Sports and Cultural Diplomacy Integration in Post-Pandemic COVID-19 International Events: Evidence from Indonesia's MotoGP Mandalika 2022 - Eljatin, M. Azim Jabar; Sumadinata, R. Widya Setiabudi; Sari, Deasy Silvya (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This study analyzes Indonesia's strategic deployment of the 2022 MotoGP Mandalika as an integrated sports-cultural diplomatic tool and examines its effectiveness in promoting tourism recovery and strengthening international relations in the postpandemic era. A qualitative research approach was employed, incorporating semistructured interviews with key stakeholders. Data triangulation was performed via primary interview data and secondary sources from August 2023-January 2025, and the impacts of the event were analyzed through the theoretical frameworks of soft power, sports diplomacy, and cultural diplomacy. The analysis revealed that the MotoGP Mandalika event successfully contributed to a 1.46% increase in regional GDP and generated an additional 4.5 trillion Indonesian rupiah in economic value. The integration of local cultural elements, including the participation of 300 SME groups and traditional performance, enhanced the event's diplomatic impact. The study identified effective multistakeholder collaboration among government agencies, international organizations, and local communities as a crucial success factor. The findings demonstrate that integrating sports and cultural diplomacy through international sporting events can effectively serve multiple national interests, from economic recovery to diplomatic relationship enhancement to national security. The successful implementation of MotoGP Mandalika provides a model for developing nations seeking to leverage sporting events for diplomatic purposes while promoting sustainable tourism development in the postpandemic era.